TEACHING TECHNOLOGY FOR THE FORMATION OF TEACHER'S REFLECTIVE ABILITY - Umar Goyimov (Galaxy International Interdisciplinary Research Journal, 2022)
Teachers are the greatest asset of any education system. They stand at the interface — conveying knowledge, skills, and values. Pedagogical education plays an important role in the reforms and strengthening the education system of any state. Educational training has emerged global trends in education and the general needs and aspirations of the people. The quality of education depends on the quality of teachers and teaching. The article also discusses the technology of formation of the teacher's reflexive abilities and its practical significance.